Chlorogenic acid and kojic acid as anti-hyperpigmentation: in silico study - Yudantara, I Made Agus; Cahyani, Ni Ketut Nitya; Saputra, Made Agus Widiana; Dewi, Ni Kadek Diah Parwati (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2021)
Hyperpigmentation is a skin problem caused by excessive melanin production due to continuous ultraviolet (UV) radiation. Kojic acid inhibiting melanin synthesis by tyrosinase enzyme is a prevalent treatment for hyperpigmentation. This study aims to determine the potential of chlorogenic acid and kojic acid as an anti-hyperpigmentation against tyrosinase using in silico molecular docking. The docking process involved optimizing chlorogenic acid and kojic acid structures, preparing tyrosinase protein (PDB ID: 5M8O), validating the molecular docking method, and docking of chlorogenic acid and kojic acid on tyrosinase. The binding energy of chlorogenic acid and kojic acid were -4.59 kcal/mol and -3.75 kcal/mol, while the binding energy of 0TR native ligand was -5.02 kcal/mol. The interaction of chlorogenic acid to tyrosinase involved ARG 321 and ARG 374 residues. The results suggest that chlorogenic acid and kojic acid has the potential as anti-hyperpigmentation agents through inhibition of the tyrosinase enzyme.